Language competency in autism: a scientometric review - Alasmari, Muhammad; Alduais, Ahmed; Qasem, Fawaz (Frontiers in Psychiatry, 2024)
The study of atypical language acquisition in children with, autism spectrum disorder (ASD) is crucial for both practical and theoretical reasons. Understanding the course of language development in ASD can inform potential interventions and treatments while shedding light on the necessary conditions for language development in typically developing children. This scientometric review aims to provide a comprehensive overview of the research landscape in this field, identifying trends, patterns, and knowledge gaps. The methods employed in this review comprise a systematic search of three major databases: Scopus (5,026 documents), Web of Science (WoS; 4,570 documents), and Lens (3,235 documents). The analysis includes bibliometric indicators such as knowledge production size by year, country, university, source, subject area, author, and citation. Scientometric indicators consist of burst detection, silhouette, clusters, citation, and co-occurrence of keywords. The analysis reveals clusters focusing on various aspects of language development in ASD, such as motor skills, parental communication strategies, cognitive processes, and genetics. Key clusters include the relationship between fine motor gestures and language usage patterns, the role of expressive language skills and maternal gesture use, and the effectiveness of online parent training modules for improving prelinguistic predictors. Other noteworthy clusters explore the importance of core language skills, the role of natural language input and syntactic complexity, and the genetic underpinnings of language abilities in high-functioning adults with ASD. In conclusion, this scientometric review highlights the top 10 clusters and their respective Silhouette values, providing valuable insights into language acquisition in ASD. These findings have important implications for guiding future research directions and informing the creation of targeted and effective interventions to support language acquisition in this population.